The macroeconomic management of foreign aid : opportunities and pitfalls - Isard, Peter; International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Argues that the Millennium Development Goals (MDGs) cannot be achieved without a substantial "scaling up" of foreign aid. This book shows how such increased aid flows must be managed effectively to ensure the greatest benefit.
Foreign aid and macroeconomic management: overview and synopsis of key lessons / Peter Isard ... [et al.] -- Session I. Aid, growth, and poverty reduction: what should aid be trying to achieve? How good is the record? Aid and growth: the current debate and some new evidence / Steven Radelet, Michael Clemens, and Rikhil Bhavnani -- Aid, growth, and poverty / Aart Kraay -- Session II. Aid absorption: recognizing and avoiding macroeconomic hazards. Analytical overview of aid absorption: recognizing and avoiding macroeconomic hazards / David L. Bevan -- High aid inflows: the case of Ghana / Shekhar Aiyar ... [et al.] -- Absorptive capacity and achieving the MDGs: the case of Ethiopia / Mark Sundberg and Hans Lofgren -- Session III. Dutch disease: where do we stand? Exogenous inflows and real exchange rates: theoretical quirk or empirical reality? / Christopher Adam -- Session IV. Aid, volatility, and stabilization policy: does aid smooth absorption or exacerbate shocks? Reliability and countercyclicality. Volatility of development aid: unpleasant bean counting / g
"Papers prepared for the seminar, which was hosted in Maputo by the Government of Mozambique during March 2005"--Foreword, p. iii.
Includes bibliographical references.
oif 31/07/15
Loan
Keywords: Economic assistance -- Congresses; Poverty -- Congresses; Fiscal policy -- Congresses; Foreign exchange rates -- Congresses